Bright Soliton and Bright–Dark Soliton Pair in an Er-Doped Fiber Laser Mode-Locked Based on In2Se3 Saturable Absorber - Wei, Qin; Han, Xile; Zhang, Huanian; Li, Chonghui; Zhang, Chao; Man, Baoyuan (Frontiers in Physics, 2021)
The output power in ultrafast fiber lasers is usually limited due to the lack of a versatile saturable absorber with high damage threshold and large modulation depth. Here we proposed a more efficient strategy to improve the output energy of erbium-doped fiber laser based on indium selenide (In2Se3) prepared by using the physical vapor deposition (PVD) method. Finally, stable mode-locked bright pulses and triple-wavelength dark–bright pulse pair generation were obtained successfully by adjusting the polarization state. The average output power and pulse energy were 172.4 mW/101 nJ and 171.3 mW/100 nJ, which are significantly improved compared with the previous work. These data demonstrate that the PVD-In2Se3 can be a feasible nonlinear photonic material for high-power fiber lasers, which will pave a fresh avenue for the high-power fiber laser.